Islamic private equity alternative investment structure based on commodity Murabahah structure: analysis on the expected Hilah arguments and rebuttal grounds / Aiman Aizuddin Abdul Rashid and Rusni Hassan - Abdul Rashid, Aiman Aizuddin; Hassan, Rusni (Academy of Contemporary Islamic Studies (ACIS), Universiti Teknologi MARA (UiTM), 2023)
This study seeks to address the challenges currently encountered by the Islamic Private Equity (IPE) sector. It aims to establish the need for the development of a new Shariah-compliant alternative investment structure for the Islamic private equity industry to move forward by applying the underlying Shariah contract of Commodity Murabahah. In this regard, it attempts to anticipate the potential Shariah arguments that the proposed Alternative Structure may face against the utilization of such proposed Commodity Murabahah structure especially on the grounds of hilah (ruses/legal stratagems) and establish the relevant and appropriate rebuttal to counter such arguments.